Kajian Teologis Konsep Pemberitaan Injil Berdasarkan 2 Korintus 5: 18-21 - Efrayim Ngesthi, Yonathan Salmon; Munandar, Aris; Zacheus, Soelistiyo Daniel; Dwikoryanto, Matius I Totok (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2021)
Preaching the gospel in believers requires responsibility and courage to actualize it. But many people do not understand that evangelism is God's way of working with people to bring a message of reconciliation to people. Through descriptive qualitative methods with a literature study approach, it can be concluded that God's people must be able to understand that there is a heart of God in saving humans in God's mission of reconciliation for humans. Furthermore, God's people can also understand how God entrusts the task of serving missions to be a priority and responsibility to do, because being a messenger of Christ for the salvation of others is a way for believers to respond to God's call to be a blessing to this world.AbstrakMemberitakan injil dalam diri orang percaya memerlukan tanggung jawab dan keberanian dalam mengaktualisasi. Namun banyak orang tidak memahami bahwa penginjilan adalah cara Allah bekerja sama dengan manusia membawa pesan pendamaian bagi manusia. Melalui metode kualitatif deskritif dengan pendekatan studi literature dapat disimpulkan bahwa umat Tuhan harus dapat memahami bahwa adanya hati Allah dalam menyelamatkan manusia dalam misi pendamaian Allah bagi manusia. Selanjutanya umat Tuhan dapat mengerti juga bagaimana Allah Mempercayakan tugas pelayanan misi menjadi prioritas dan tanggung jawab untuk dikerjakan, sebab menjadi utusan Kristus bagi keselamatan orang lain adalah merupakan cara orang percaya merespon panggilan Tuhan untuk menjadi berkat bagi dunia ini.